Effectiveness of E-Modules Based Learning on Project Based Learning in Chemistry Learning: A Meta-analysis - Risnawati Risnawati; Diah Purwaningsih (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the effectiveness of Project-Based Learning-based E-modules in Chemistry Learning. This type of research is quantitative research with a meta-analysis method. The inclusion criteria in this study are the research was obtained through the google scholar database; Mendeley, ScienceDirect and ERIC, the research must be indexed by SINTA, Web of Science or Scopus,  the research topic must be relevant,  the research must be published in 2021-2024, the research must have a value of (r), (t) or (f), the research must have N ≥ 25. The data analysis technique in this study is with the help of the JSAP application version 0.16.3. The results of this study concluded that (a) the 19 studies analyzed were heterogeneous and normal, there was a significant influence of project-based learning-based e-modules with strong categories (p < 0.05; rRE= 1.06); and in this study, there is no publication bias. These findings show that there is a positive influence of project-based learning-based E-Module learning in chemistry learning